THUNDERSTORM AND RAINFALL FREQUENCIES OVER SINDH, PAKISTAN FOR THE PERIOD 1961-2010 - Sadiq, N. (The Nucleus, 2013)
The study is aimed to analyze the fifty years (1961-2010) data of Thunderstorm (TS) and Rainfall (RF) frequencies for the Sindh province via nine meteorological stations that are almost unevenly distributed over the region. Monthly, overall seasonal and station wise seasonal percentages are calculated and analyzed. In addition, percentage frequency comparison of TS and RF are also incorporated. Both the activities are observed with greatest frequency (59%) in monsoon while annual diversity of TS is found greater than RF. During monsoon period, Badin is the most while Jacobabad and Larkana are the least affected reported stations by frequent storms along with rainfall, respectively.